Modeling and Simulation of the Photovoltaic Cells for Different Values of Physical and Environmental Parameters - Azem Hysa (Emerging Science Journal, 2019)
Both research and technological development in the area of renewable energy sources are necessary to account for the increase in energy demand and environment problems in the world. The photovoltaic (PV) cell has been described by non-linear outputs characteristics in current-voltage and power-voltage. This outputs is affected by various effects such as; series resistance ( ), shunt resistance ( ), solar irradiance and temperature. In this paper the effect of variation of parameters has been studied such as series resistance ( ) and shunt resistance ( ) of the diode in the photovoltaic cell and these effects could be seen in the Current-Voltage (I-V) and Power-Voltage (P-V) characteristic curves. In this paper also has been studied the effect of variation of the environmental parameters such as solar irradiance and temperature. Results show that a higher temperature at constant solar irradiance produces a decrease power. So the voltage and the photovoltaic cell output power tend to decrease at higher temperatures, but there is no noticeable effect on the photovoltaic cell current. Thus, it is important to keep the cell temperature as low as possible, because higher temperatures have negative effect on output power of photovoltaic cell. On the other hand, the effect of solar irradiance on photovoltaic cell, it reveals that higher solar irradiance gives higher current and higher power. Shunt resistance has significant effect on the operating characteristic curves of PV cells as low power output is recorded if the value of shunt resistance varies from 0.07 ohms to 1700 ohms. Finally, I have presented power-voltage characteristic curves and current voltage characteristic curves of photovoltaic cell for different solar irradiance in Shkoder, Tirana and Vlore.